Chromatographical fractionation guided by antioxidant activity of Morinda citrifolia - Rasha Saad; Muhammad Aqil; Eddy Yusuf; FadliAsmani (International Journal of Pharmacy and Analytical Research, 2014)
Morinda citrifolia Linn. belongs to family of Rubiaceae. Characteristically, the plant is ascribable by its elongated trunk with 8-10 inches long bright green leaves. The leaves are opposite, pinnately veined and glossy. Initially, the subject plant specimen was further authenticated and identified taxonomically by Forest Research Institute Malaysia (FRIM) and have been granted with the specimen number of PID140314-10 for future research. The dried leaves were then extracted with methanol by maceration-ultrasonication extraction method. Methanolic crude extracts were fractionated on open column chromatography with ethyl acetate-hexane (50:50) as eluate. Ten fractions were collected and analyzed for antioxidative activity assay using in-vitro model of 1, 1- Diphenyl-2-Picrylhydrazyl (DPPH) radical. The results showed that fraction number three exhibited considerably high antioxidative activity comparing with the standard dose of marketed tocopherol. The IC30value of fraction three was 100mg/ml. This fraction together with fraction two, four, eight and nine were subjected to quantitative and qualitative analysis of phytochemical screening. Results for fraction three shows that five of seven phytochemical screened for were present. They are: alkaloid, flavonoid, glycoside, tannin and anthraquinone. Quercetin, tannic acid and emodin reagent were used as standard for calibration of total flavonoids, tannins and anthraquinone content respectively. The quantification of total flavonoid, tannin and anthraquinone content showed 2.74mg/g quercetin, 47.62µg/g tannic acid and 1.142mg/g emodin equivalent respectively, the study indicates that the leaves of Morinda citrifolia Linn. serves as a potent source of natural antioxidant activity and exhibit the highest flavonoid, tannin and anthraquinone content.